2007
DOI: 10.1364/oe.15.002779
|View full text |Cite
|
Sign up to set email alerts
|

Control of the filamentation distance and pattern in long-range atmospheric propagation

Abstract: We use the double-lens setup [10, 11] to achieve a 20-fold delay of the filamentation distance of non-chirped 120 fs pulses propagating in air, from 16m to 330m. At 330m, the collapsing pulse is sufficiently powerful to create plasma filaments. We also show that the scatter of the filaments at 330m can be significantly reduced by tilting the second lens. To the best of our knowledge, this is the longest distance reported in the Literature at which plasma filaments were created and controlled. Finally, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…These effects can significantly alter the efficiency of the process. The filamentation of the laser beam can be checked by employing beam-smoothening techniques [23].…”
Section: Discussionmentioning
confidence: 99%
“…These effects can significantly alter the efficiency of the process. The filamentation of the laser beam can be checked by employing beam-smoothening techniques [23].…”
Section: Discussionmentioning
confidence: 99%
“…(8) shows the result of using a negatively chirped Gaussian pulse (W 0 = 1.4 cm) with the scaled turbulence parameters W 0 / 0 = 1 and σ 2 R = 1. 5. The temporal compression of the pulse keeps the power relatively constant over 6 Z R .…”
Section: Channeling With Atmospheric Extinctionmentioning
confidence: 99%
“…With the advent of laser pulses exceeding gigawatts of peak power, nonlinear self-focusing in air and laser filamentation became possible. Numerous studies have shown that filamentation can produce extended optical and plasma structures in air [3][4][5][6][7]. Filamentation allows the laser pulse to propagate many vacuum Rayleigh lengths at high intensity due to a balancing of nonlinear self-focusing, plasma defocusing or harmonic generation, and nonlinear dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…In previous works, experimental research in the field of filamentation created filaments typically a few metres in the laboratory [17][18][19] and over hundreds of metres Correspondence to: S. Li and M. Jin, Institute of Atomic and Molecular Physics, Jilin University, Changchun, Jilin Province 130012, China. Email: suyu11@mails.jlu.edu.cn, mxjin@jlu.edu.cn at a range of few kilometres in the atmosphere [20][21][22] , making the remote sensing possible. Since the intensity of plasma fluorescence is related to that of the laser beam, plasma fluorescence spectra along the propagation path can be used to characterize the femtosecond filamentation process.…”
Section: Introductionmentioning
confidence: 99%